1988
DOI: 10.1159/000181005
|View full text |Cite
|
Sign up to set email alerts
|

The Use of SMS 201-995 (Somatostatin Analogue) in Insulinomas

Abstract: A 76-year-old man, a known case of insulinoma, was well controlled for 11 days on 50 µg SMS 201-995 every 12 h; clinical recovery was immediate with normalization of blood sugars and C-peptide levels. The potential value of this new drug in the management of insulinomas is illustrated by this case and by 11 additional case reports which are reviewed. A rise in C-peptide levels during treatment without concomitant hypoglycaemia might be the first indication of a loss of control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
4
3
0
Order By: Relevance
“…The effective dose was unrelated to body mass index, age, serum creatinine or insulinoma size and had to be adapted to each patient's blood glucose levels. There are reports of insulinoma patients who need only 25 or 50 µg/day octreotide to normalize blood glucose levels 12,25,26 . Similarly to what has been reported previously in acromegaly, we did not observe tachyphylaxis in our patients on long‐term treatment 27 .…”
Section: Discussionsupporting
confidence: 89%
“…The effective dose was unrelated to body mass index, age, serum creatinine or insulinoma size and had to be adapted to each patient's blood glucose levels. There are reports of insulinoma patients who need only 25 or 50 µg/day octreotide to normalize blood glucose levels 12,25,26 . Similarly to what has been reported previously in acromegaly, we did not observe tachyphylaxis in our patients on long‐term treatment 27 .…”
Section: Discussionsupporting
confidence: 89%
“…The treatment was effective in all SSTR 2 positive patients and in a few SSTR 2 negative ones, while no relation between treatment effectiveness and the expression of SSTR 5 was observed (40). These results are in concordance with other case reports and smaller series of insulinoma patients reported in the literature (4145). In glucagonoma patients SST analog treatment is indicated to reduce the symptoms related to the characteristic skin rash (necrolytic migratory erythema) or diarrhea (46–50).…”
Section: The Symptomatic and Biochemical Effects Of Sst Analogssupporting
confidence: 93%
“…Recently, in patients with acromegaly, the availability of the long-acting octreotide formulation, octreotide LAR, has improved patients' compliance to long-term treatment [8]. In several reports of insulinoma, octreotide was used for the control of hypoglycemia and body weight prior to surgery [1,3], or because of failure to localize the tumor [1,[4][5][6]. Octreotide has also been used to control hypoglycemia in cases of malignant insulinoma [1].…”
Section: Of Somatostatin Receptors (Octreoscan)mentioning
confidence: 99%
“…The somatostatin analogue, octreotide, is known to suppress the secretion of insulin in healthy subjects as well as in some patients with insulinoma. Several studies have reported the usefulness of octreotide in patients with benign and malignant insulinomas [1][2][3][4][5][6][7]. However, as octreotide is a shortacting formulation, several subcutaneous injections per day are required for effective treatment.…”
mentioning
confidence: 99%